The relationship between gonadotropin and sexual behaviour of male Trichogaster trichopterus (Pallas) - Mananos, E; Zohar, Y; Degani, G (Indian Journal of Fisheries, 2011)
The levels of gonadotropin (GtH-II) in the plasma and pituitary, and of the steroids testosterone (T) and progesterone (P) in the plasma and testes, were measured in male blue gourami (Trichogaster trichopterus) during sexual behaviour (before and during nest building and during courtship). In the pituitary of nest-building and courting males, the levels of GtH-II (1854 ±112 and 1520±112 ng/mg protein, respectively) were higher than in males that were not building nests (10781112 ng/mg protein); while in the plasma, GtHII levels were 7 ± 1.5, 6 + 1 . 1 and 4.6 ±1.1 ng/ml, respectively. The same pattern was found in the levels of plasma T:3.6 ± 1.0, 2.4 ± 0.8 and 1.5±0.8 ng/ml, respectively), though no significant difference was found in the testes. Similarly, the levels of P in the testes were 4 ± 1.0, 3.8 + 0.9 and 2 ± 0.9 ng/ ml, respectively. The relationship between GtH-II and male sexual behaviour is discussed.